PENGARUH GREEN MARKETING MIX TERHADAP PURCHASE INTENTION DENGAN ENVIRONMENTAL KNOWLEDGE SEBAGAI VARIABEL MODERATOR: SURVEI PADA TOKO FURNITURE MODERN - Tuanku Raflie Damarayudha; Andi Muhammad Sadat; Ika Febrillia (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study is to determine the effect of green product on purchase intention, the effect of green price on purchase intention, the effect of green place on purchase intention, the effect of green promotion on purchase intention, the effect of green product on purchase intention with environmental knowledge as a moderator variable, the influence of green price on purchase intention with environmental knowledge as a moderator variable, the effect of green places on purchase intention with environmental knowledge as a moderator variable, the effect of green promotion on purchase intention with environmental knowledge as a moderator variable. The data collection method used is a survey method with an instrument in the form of a questionnaire. The research sample at least 200 respondents who live in greater Jabodetabek, aged 17 years and over and know the IKEA brand. Software used in data analysis is SPSS and SEM (Structural Equation Model) from AMOS version 26